1994
DOI: 10.1111/j.1365-2052.1994.tb00409.x
|View full text |Cite
|
Sign up to set email alerts
|

Restriction fragment length polymorphism (RFLP) of exon 2 of the MhcBibi‐DRB3 gene in American bison (Bison bison)

Abstract: Polymerase chain reaction (PCR) primers specific to exon 2 of the bovine lymphocyte antigen (BoLA)-DRB3 gene were successfully used to amplify the equivalent region in 469 American bison (Bison bison). In domestic cattle, alleles of DRB3 are assigned through a restriction fragment length polymorphism (RFLP) analysis of the patterns of fragment lengths observed after digestion with the restriction enzymes RsaI, BstYI and HaeIII. In bison, using the same procedure, the observed RFLP patterns provided evidence fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…1). Restriction fragment patterns (Morris et al 1994), three of which (a, f, and m) were also found in European bisui. In American bison, patterns k, q and s were not observed.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…1). Restriction fragment patterns (Morris et al 1994), three of which (a, f, and m) were also found in European bisui. In American bison, patterns k, q and s were not observed.…”
Section: Resultsmentioning
confidence: 81%
“…2). RFLP pattern i was shown to be present in three American bison herds (Morris et al 1994) and, in one of the herds, the frequency of the allele was estimated to be 0.540. Pattern t (111, 39, 30, and 104 bp), which was absent in cattle and present in five American herds studied by these authors, is identical to cattle pattern m (111, 69, and 104 bp) with an additional restriction site (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations